Superabsorbent polymer and its effect on maize germination, emergence and genetic diversity of rhizosphere microorganisms - Ondreičková Katarína; Hrčková Katarína; Klčová Lenka; Cilík Peter; Gubiš Jozef (Agriculture, 2023)
The application of superabsorbent polymer (SAP) for seed coating of agricultural crops is an innovative and promising method to effectively reduce plant stress during dry periods and thereby contribute to sustainable agriculture. However, due to the lack of experiments using SAP in field conditions in Central Europe, we focused on determining the effect of synthetic SAP, which was used for coating maize seeds, on the germination and emergence of these plants as well as on determining its impact on the genetic diversity of microbial communities in the maize rhizosphere for two consecutive years. The results showed that the growth parameters of coleoptiles and root systems of germinating maize plants at the very early development stage were biased in favour of SAP-coated seeds, and some values were statistically higher in the second year of evaluation. Similar observations were recorded in the assessment of maize emergence parameters. Also, these values were better when using SAP-coated seeds compared to the untreated controls. Plant height, dry weight, leaf tip number, and the Soil Plant Analysis Development (SPAD ) value were statistically higher in the second year of evaluation. The rhizosphere bacterial and fungal genetic diversity results did not confirm statistically significant differences between the SAP-coated and control maize seeds. They concern both alpha diversity indices and the results from multivariate statistical methods. Principal coordinate analysis results with cluster analysis show that the main factor influencing the microbial diversity in the maize rhizosphere was the collection date, especially the year of sampling than t he use of SAP-coated seeds.